Three-dimensional accuracy of different techniques and materials for interocclusal bite registration - Philipp-Cornelius Pott; Carolin Becker; Simone Schaumann; Lara Bühnen; Meike Stiesch; Michael Eisenburger (Mashhad University of Medical Sciences, 2024)
Objective: This study aimed to compare the precision of a temporomandibular joint (TMJ)-related bite-registration technique with the occlusion-related registration technique using various polyvinyl siloxane materials. Methods: The interocclusal relation of 40 patients was transferred to stone casts by bite registrations using polyvinyl siloxane materials with different Shore harnesses (SH) values including Registrado clear (SH=70 A), Registrado xtra (SH=51 D) and Registrado scan (SH=90A). A joint-related registration technique (called the Gerber technique or gothic arch tracing) was also applied in all patents. The clinical contact situation and the contacts on stone casts were marked and transferred to a 3D-measuring software. The deviation of the occlusal contacts on the stone casts to the clinical reference was measured and compared between the registration methods.  Results: There was no statistically significant difference in contact deviation values between different types of registration methods (P=0.093). However, the frequency of missing contacts was significantly greater in the Gerber technique compared to the occlusion-related bite registrations (P<0.001). Gerber technique revealed greater deviations of the contact points in subjects with pain in TMJ and masticatory muscles. Irrespective of the registration technique, the patient-related factors including orthodontic pretreatment, treatment of TMD with occlusal splints, pain on palpation, joint noises, and restricted mandibular movement did not significantly affect the degree of occlusal contact deviation (P>0.05).Conclusions: The hardness of the polyvinyl siloxane materials for occlusion-related bite registration did not affect the precision of the registration techniques in dentulous patients. Polyvinyl siloxane materials should be preferred for joint-related registration in TMD patients